Risk of dementia and death in community-dwelling older men with bipolar disorder. (August 2016) - Almeida, Osvaldo P.; McCaul, Kieran; Hankey, Graeme J.; Yeap, Bu B.; Golledge, Jonathan; Flicker, Leon
Abstract : Background: Bipolar disorder has been associated with cognitive decline, but confirmatory evidence from a community-derived sample of older people is lacking. Aims: To investigate the 13-year risk of dementia and death in older adults with bipolar disorder. Method: Cohort study of 37 768 men aged 65–85 years. Dementia (primary) and death (secondary), as recorded by electronic record linkage, were the outcomes of interest. Results: Bipolar disorder was associated with increased adjusted hazard ratio (HR) of dementia (HR = 2.30, 95% CI 1.80–2.94). The risk of dementia was greatest among those with <5 years of history of bipolar disorder or who had had illness onset after 70 years of age. Bipolar disorder was also associated with increased mortality (HR = 1.51, 95% CI 1.28–1.77). Competing risk regression showed that bipolar disorder was associated with increased hazard of death by suicide, accidents, pneumonia or influenza, and diseases of the liver and digestive system. Conclusions: Bipolar disorder in later life is associated with increased risk of dementia and premature death.